1970
DOI: 10.3329/bjsir.v45i2.5704
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Mass Propagation of <i>Mimosa pudica</i> L., Using Shoot Tip and Nodal Explants

Abstract: An efficient protocol was established for in vitro mass propagation of a valuable medicinal shrubby plant, Mimosa pudica Linn., from shoot tip and nodal explants. Optimum in vitro shoot induction was observed from nodal explants on MS basal medium supplemented with 1.5 mg/l BAP + 0.5 mg/l NAA, in which 88.2% of the explants produced 9 shoots per culture within 3-4 weeks. Repeated subcultures in the same medium, resulted rapid shoot multiplication with 20.4 ± 1.20 shoots per culture within 12 weeks. The healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
1
6
1
Order By: Relevance
“…The results found in our study show that the adventitious rooting developed at in vitro phase under stimulus of auxins was irrelevant, since both rooted and non-rooted micro-cuttings of M. pudica presented high survival rate to acclimatization. Moreover, the success in the acclimatization phase found in the present study was better than those found in other studies with M. pudica (Hassan et al, 2010;Ramesh et al, 2013). The plantlets mortality observed during the in vitro rooting stage was higher than in acclimatization phase.…”
Section: The Procedures Of Acclimatizationcontrasting
confidence: 89%
See 3 more Smart Citations
“…The results found in our study show that the adventitious rooting developed at in vitro phase under stimulus of auxins was irrelevant, since both rooted and non-rooted micro-cuttings of M. pudica presented high survival rate to acclimatization. Moreover, the success in the acclimatization phase found in the present study was better than those found in other studies with M. pudica (Hassan et al, 2010;Ramesh et al, 2013). The plantlets mortality observed during the in vitro rooting stage was higher than in acclimatization phase.…”
Section: The Procedures Of Acclimatizationcontrasting
confidence: 89%
“…Differences were observed for the Acacia mangium Willd for which the supplementation of Bianchetti et al 425 0.5 µM NAA to the culture medium for multiple shoots induction (4 µM BAP) was harmful, leading to the reduction of shoots proliferation (Shahinozzaman et al, 2012). For M. pudica cultures, Hassan et al (2010) found high multiplication rates when 6.6 µM BAP and 2.6 µM NAA were combined, although the response percentages have been smaller. Also, studying M. pudica micropropagation, Ramesh et al (2013) achieved an increase in number of shoots/explant using simultaneously IAA and NAA in culture media supplemented with BAP.…”
Section: Cultured In Vitromentioning
confidence: 83%
See 2 more Smart Citations
“…The highest percentage (96%) of root formation, maximum number of roots (8.70±0.42) and highest length (4.64±0.23) of roots were recorded in this medium within three weeks of inoculation (Plate 5). Several earlier researchers (Khalekuzzaman et al, 2008, Biwas et al, 2009, Hassan et al, 2010, Das et al, 2008, Karthikeyan et al, 2009 reported root induction in different medicinal plants by using IBA in MS and modified MS. In the present study it was observed that IAA and NAA were less effective for root induction in E. alba.…”
Section: Resultsmentioning
confidence: 99%